Quasi Z‐source inverter with switched‐capacitor‐inductor for enhancing boost factor - Jamal Abbasi Bolaghi (Wiley, 2021)
Abstract Two structures are proposed based on the quasi Z‐source inverter (qZSI), which can significantly raise the output voltage in applications, including photovoltaic and fuel cells, in which the input voltage is low. The proposed inverters provide a continuous input current and reduce the voltage stress on capacitor. Besides, the proposed switched‐capacitor‐inductor qZSI (SCL‐qZSI) can suppress inrush current at the start up moment as this current might damage the devices. The performance of the proposed structures is investigated at different operating modes, and the voltage equations are calculated. The voltage stress on switches, the voltage stress on capacitors, the voltage stress on diodes, and the current stress on inductor, as well as the average DC‐link current, the gain voltage (G), and the boost factor (B) of the proposed inverters, are analysed and derived. They are then compared with similar converters. To confirm the performance of the proposed converters, a laboratory sample of converters is made, which with output voltages, capacitors voltages, input and output current for the proposed converters. The DC‐link (Vi) voltage is 95 with boost factor 1.6 for SCL‐qZSI, and the DC‐link voltage is 216 with boost factor 3.6 for the enhance switched‐capacitor‐inductor qZSI (ESCL‐qZSI), which confirms the relationships obtained from the proposed converters. Also, the abbreviation for this paper is shown in table 1.